Analisis Fraud Pentagon Terhadap Tindakan Kecurangan Laporan Keuangan Dengan Penggunaan Model Beneish - Aprilya Dwi Yandari; Isnani Yuli Andini (Jayapangus Press, 2020)
Fraudulent financial statements are a form of the category of fraud that often occurs. Another category of fraudulent financial statements is the category of fraud with the smallest frequency value, but will later result in a greater loss value than other categories. Pentagon fraud will be used in research, because this theory is a theory of refinement of triangles and diamonds. So that the pentagon fraud theory has a new element that is not present in both theories, namely arrogance which is not widely used in detecting fraudulent financial statements. The research objective is to provide information for shareholders, stakeholders, and other stakeholders about the pentagon fraud test against financial statement fraud using the Beneish Model detection tool in banking companies. The population in this study is all banking companies listed on the IDX in 2016-2018 totaling 43 companies. The sample in this study used purposive sampling, namely all banking subsectors listed on the IDX in 2016-2018 which consistently reported their finances. The data analysis technique used is multiple regression with the coefficient of determination, model feasibility test, partial test and logistic hypothesis test. Based on the research results, the variable of the effectiveness of supervision has no effect on fraudulent financial statements. The replacement of the chairman of the internal auditor has no effect on fraudulent financial statements. Financial stability has no effect on fraudulent financial statements. External pressure has no effect on fraudulent financial statements. Changes in company accounting policies have no effect on fraudulent financial statements.